FINANCIAL STRUCTURE AND ECONOMIC GROWTH NEXUS IN EMERGING ECONOMICS IN AFRICA - Dabi, Rowland; Sari, Maya; Nugraha, Nugraha; Disman, Disman; Alghifari, Erik (Jurnal Riset Bisnis dan Manajemen, 2024)
The study investigates specifically the relationship between Gross Domestic Product (GDP), total stock market traded, market capitalization, private credit by deposit bank, human capital, foreign direct investment, population and trade openness (imports plus exports) and economic growth (GDP per capita). We use the extended endogenous growth model with specifications by employing dynamic panel data methodology. Our empirical application of the dynamic panel model to the finance–growth nexus is based on an unbalanced panel dataset of 29 middle-income African countries1 over the period 1990 – 2019 obtained from World Development Indicators. The findings revelead that financial development exerts significant and positive impacts on economic growth. The overall development of the financial system is essential for enhancing economic outcomes. Therefore, attempts at achieving some fine balance between a bank-based system and a market-based system are trivial to growth.